Punta morada - International Potato Center (2025)
This short video raises awareness about purple top disease in potato, highlighting key symptoms and its negative effects on plant growth and tuber yield. The video emphasizes the importance of early identification and proper crop management to reduce production losses associated with insect-transmitted diseases. By promoting basic plant health knowledge, the video contributes to improved crop protection, productivity, and food security in potato-based farming systems.